Lithium Batteries Take To The Road. - Voelcker, J. (IEEE spectrum)
Lithium-ion cells are poised to take an increasing share of the auto battery market, just as electric drive seems set to begin a long, slow climb to become, at last, a serious power-train option. But what's rarely understood is how much that second revolution depends on the first.